Analisis Hubungan Kausalitas antara Pertumbuhan Ekonomi dan Pengeluaran Pemerintah di Indonesia - Harjanto, Sigit; Wahyudi, Setyo Tri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This research aims to find out how the relationship of causality between economic growth and government expenditure. Government expenditure is divided according to the functions of the general services, the functions of defense, security and public order, the economic function and the function of education. Using the Toda-Yamamoto CausalityÂ Test,Â thatÂ Â can be used in time-series data with different levels of integration, we found unidirectional causality relationship between economic growth and government expenditure in which government expenditure affect economic growth that supports Wagnerâs Law. On expenditure by function,Â weÂ found the relationship that supportsÂ Keynessian aproach between economic growth and the government expenditure in economic functions . In another functionsÂ ofÂ governmentÂ expenditure weÂ not found the existence of a relationship of causality with economic growth.Keyword: Economic Growth, Government Expenditure, Toda-Yamamoto Causality Test